АНАЛИЗ ЗАВИСИМОСТИ КПД КОМБИНИРОВАННОЙ СИСТЕМЫ ЭНЕРГОПИТАНИЯ ОТ ПАРАМЕТРОВ УПРАВЛЕНИЯ - Шидловский, А.К.; Павлов , В.Б.; Павленко, В.Е. (Інститут електродинаміки НАН України, Київ, 2016)
The analysis of the relation of combined system power suppyl efficiency with control parametres of the power semi-conductor converter and a dynamo is made. The optimal loading modes, that allowing to receive the greatest possible efficiency of system in all control band, are determined. References 4, figures 4.